2007
DOI: 10.1111/j.1439-0507.2007.01451.x
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological survey of tinea capitis in Sarajevo, Bosnia and Herzegovina over a 10‐year period

Abstract: The aim of this study was to determine the incidence and aetiological agents of tinea capitis in Sarajevo area, Bosnia and Herzegovina, during a 10-year period (1997-2006). A total of 707 patients with suspected dermatophyte infections of scalp was analysed. Tinea capitis was determined in 241 (34.1%) of these patients, in whom causative agents were identified in 209 (29.6%). Zoophilic dermatophytes (91.8%) prevailed over anthropophilic (7.2%) and geophilic (1.0%) dermatophytes. Microsporum canis was the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 35 publications
0
11
1
Order By: Relevance
“…interdigitale was the principal agent of tinea pedis in our investigation. We can see high prevalence of T. rubrum in many investigations that have reported from different places in Asia , but this species caused only 4% of total infection in present study. Recent epidemiological surveys of dermatophytoses in European countries have approved the increasing of tinea unguium while this clinical form of infection included only 4% of dermatophytoses in the present study.…”
Section: Discussioncontrasting
confidence: 60%
“…interdigitale was the principal agent of tinea pedis in our investigation. We can see high prevalence of T. rubrum in many investigations that have reported from different places in Asia , but this species caused only 4% of total infection in present study. Recent epidemiological surveys of dermatophytoses in European countries have approved the increasing of tinea unguium while this clinical form of infection included only 4% of dermatophytoses in the present study.…”
Section: Discussioncontrasting
confidence: 60%
“…(ii) There is no gender difference or even male preference before puberty, but females predominate afterwards and accentuate further in senile ages. Tinea capitis is more common in boys of school‐age and adolescent ages but affects 3–4 folds more adult women than men, especially after menopause 36,37 . Trichotillomania affects slightly more boys in pre‐school ages, but more girls in adolescent ages, and show distinct female preponderance in adult ages (4 : 1) and most extreme in the oldest group (15 : 1) 99 .…”
Section: Gender Dimorphism In Skin Diseasesmentioning
confidence: 99%
“…Tinea is a prepubertal disease and it was found that higher rate of infection is in children under 11 years of age. In previus reports, Yehia (1980), Raccurt et al, (2009) London had a frequency of 71.3% of scalp infections in male and 28.7% in females with children in the majority, in Sarajevo the infection is more in male children less than 10years of age (56.5%) (Prophic, 2008).The deficiency of sebum which acts as a fungistic factor will favor infectionand the presence of dermatophytes on healthy skin may be due to commensalisms. Factors such as high blood sugar level and the presence of fatty acid in skin may determine the presence of these organisms and explain their gradual decline with advancing age (Clayton 1977;Martinez, 1980 ).…”
Section: Discussionmentioning
confidence: 97%
“…In this study the prevalence rate is higher (48.9%)compared to the results (9%) from 5 primary schools in Bengzazi, a rural Kuwait (Al-Mosawi et al, 1993). Ajao and Akintunde (1985)found a prevalence rate for clinical infections among school children in Ile Ile to be 14.02% and in urban and rural school in and around Lusaka was 16.8% (Simpanya,1989), and in Sarajevo it was 52.6% of the children that were infected (Prophic, 2008). The relatively high rate of the infection in the community surveyed could be attributed to lack of adequate information on the disease and the possible misconception about the cause, low standard of living, overcrowding and poor hygiene as reason for the apparent increase in the spread of the disease.…”
Section: Discussionmentioning
confidence: 99%